Situation Report: Romania, 20 June 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Gaston-Marin on Prices CC Executive Committee Approves Building of Hydroelectric Station Professional and Vocational High Schools Ceausescu Postpones Bonn Visit? Romania and Britain Sign Trade and Co-operation Agreements US Export-Import Bank President Visits Bucharest